TAX COURT DECISION ON THE PRIMARY DISPUTE OF EXPORT VALUE-ADDED TAX BASE - Hastanti Agustin Rahayu; Neni Pancawati; Syarifudin Syarifudin (Berkala Akuntansi dan Keuangan Indonesia, 2022)
This study analyzes the content of the tax court decision on the primary dispute on the imposition of the Export VAT tax. A qualitative content analysis method with an inductive qualitative approach was applied. The qualitative content analysis was performed on 17 (seventeen) minutes of tax court decisions from the 2017 decision year, with two categories of Export VAT base disputes, namely corrections to the Export VAT base for foreign currencies and corrections to the Export VAT base for affiliated transactions. Whereas in the category of tax primary disputes, the export VAT base on foreign currency maintains the tax authorities' correction. This is related to the concept of substance over form, as well as the VAT Law's regulations in calculating the VAT base in rupiah, which is exchanged at the PMK rate upon acknowledgment of the BKP or JKP submission transaction. Meanwhile, the category of tax primary dispute Export VAT base on affiliated transactions rejects the taxpayer's application because the comparison company data does not comply with the OECD Transfer Pricing Guideline and does not meet the arm's length principle. The Tax Court Judge's decision is following Article 7 of Law no. 14/2002. In which, the decision is based on the results of the assessment of evidence, the relevant tax laws and regulations, and the judge's conviction which is based on the assessment of the evidence and following the tax laws and regulations.